Reprint of "structural diversity of cobalt(II) coordination compounds involving bent imidazole ligand: A route from 0D dimer to 3D coordination polymer" - Schlechte, Laura; Bon, Volodymyr; Gruenker, Ronny; Klein, Nicole; Senkovska, Irena; Kaskel, Stefan (Polyhedron, 2013)
Mixed ligand approach could be successfully applied to design porous three-dimensional coordination polymers, involving 1,3-bis(imidazol-1-yl)benzene (1,3-bib) as ligand. Five novel Co(II) compounds with different dimensionality have been synthesized. Utilizing only 1,3-bib in the solvothermal reaction with Co(II) salts, only molecular dimer Co2(bib)2Cl4 or 1D polymer Co2(1,3-bib)2(NO3)2 could be synthesized. Copolymerization technique using additional linear dicarboxylates 1,4-benzenedicarboxylate (1,4-bdc) or 2,6- naphthalenedicarboxylate (2,6-ndc) facilitates the formation of 2D layered coordination polymers Co(1,3-bib)(1,4-bdc) and Co(1,3-bib)(2,6-ndc). Utilizing 4,4′-biphenyldicarboxylate (4,4′-bpdc) as a co-linker, a 3D metal-organic framework Co3(1,3-bib)(4,4′-bpdc)3 (DUT-58, DUT-Dresden University of Technology), possessing two interpenetrated uninodal 8-connected frameworks, has been obtained. DUT-58 exhibits a specific surface area of 1208 m2/g and adsorbs 27 mg/g hydrogen (maximum excess value at 30 bar and 77 K), 0.18 g/g n-butane (at 293 K) and 72 mg/g methane (maximum excess value at 60 bar and 298 K).
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cobalt(II); Imidazole ligand; Interpenetration; Metal-organic framework; Microporous material